Análise genômica das principais raças de ovinos brasileiras - Gouveia, João José de Simoni (2013)
The Brazilian locally adapted sheep breeds, also known as native and creole, are descendant from animals brought during the settlement period and, since then, are been subjected to evolutive (both systematic and non systematic) processes, what resulted in the formation of highly adapted genotypes to the diverse environmental Brazilian conditions. Although these breeds don’t posses the same productive potential when compared with the exotic improved breeds, they are considered extremely important from a social and cultural point of view. Moreover, the locally adapted breeds are essential for the maintenance of traditional production systems. The optimization of the utilization of naturalized genetic resources depends on a deep knowledge of these populations, and then, the morphological, productive and molecular characterizations are essential to the success of conservation and utilization of these locally adapted genotypes. Therefore, the principal aim of this thesis was to deepen molecular the knowledge of the three main locally adapted Brazilian sheep breeds: Brazilian Creole, Morada Nova and Santa Ines. Thus, Chapter I entitled "Identification of selection signatures in livestock species" is a literature review that is proposed to describe the main effects of natural/artificial selection in the genomes of species of farm animals, present the main methods of signature selection analysis and discuss recent advances in this area of study. Two studies were conducted and resulted in the chapters II and III of this thesis. The chapter II, entitled “Identification of selection signatures in brazilian locally adapted sheep breeds”, aimed the identification and characterization of putative genomic regions that underwent selection and the identification of candidate genes related to productive/adaptative differences between these breeds. The identification of signatures of selection was performed through two approaches: population differentiation (FST) and linkage disequilibrium (iHS and Rsb). Seventy eight genes, related to functions as: immune response, nervous system development, sensorial perception and wool/hair development were identified. The chapter III, entitled “Identification of population substructure in brazilian locally adapted sheep breeds”, aimed the identification and characterization of of genetic substructure within the three main locally adapted Brazilian sheep breeds: Brazilian Creole, Morada Nova and Santa Ines. The level of genetic differentiation between herds of the same breeds was, in general, high. Both in the Brazilian Creole and in the Santa Ines breeds the presence of distinct groups on animals could be observed, what suggests the occurrence of different ecotypes/lineages within these breeds.